Composición química de ensilaje de maíz forrajero y rechazo de banano verde en diferentes proporciones en una dieta base - Borbor Lainez, Marjorie Vanesa (2022)
The objective of this study was to evaluate the chemical composition of forage maize silage and green banana rejection in different proportions in a diet. The research was carried out at the Experimental Campus La María of the UTEQ. The treatments evaluated were T1: 50% fodder corn, 0% banana rejection; T2: 45% fodder corn, 5% banana rejection; T3: 40% fodder corn, 10% banana rejection; T4: 35% fodder maize, 15% banana rejection and T5: 30% fodder maize, 20% banana rejection; plus powder 27%, soybean paste 20% and mineral salts 0.3% supplemented in the proportional diet. Five repetitions and four treatments were used. A completely randomized design (DCA) was used. The experimental diet was evaluated: dry matter (DM), inorganic matter (IM), crude protein (CP), crude fiber (FB), gross energy (GE), crude fat (GB), neutral detergent fiber (NDF) and acid detergent fiber (FDA). The variables evaluated were subjected to analysis of variance and the TUKEY test (p<0.05) to establish significant differences. T4 and T5 reported the most significant values in DM while MI and CP showed similar values in their treatments, however T1 obtained the highest CP content (18.62%). The EB of the food the highest value was obtained by T5. In addition, the fiber fractions do not influence the composition of FDN and FDA in the analyzes carried out.